Evaluation of recycled steel properties originating from construction steel waste - Alias, Mohamad Zarif Mirza; Asnawi Subki, Nur Ezzaryn; Mansor, Hazrina; Sahol Hamid, Yazmin; Mohd Afendi, Nurizzati Hidayah; Mohd Yusoff, Mazlan; Dominic, Ellvera De Ermalina; Nasurudin, Nur Saihah (Universitas Mercu Buana, 2025)
This research presents an experiment of constructional recycled steel properties that has been remelted into component-shaped specimens using green sand casting. A series of tensile, compressive and toughness tests were conducted. Then, specimens were observed using Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray (EDX) for microstructure analysis and chemical composition determination. This experiment was done to determine whether the recycled steel quality met the industrial standards. All tests were conducted at Universiti Teknologi MARA (UiTM), providing data on the stress-strain relationship and toughness of recycled steel. The results indicated that recycled steel exhibited tensile characteristics below the standard strength range required by Eurocode. The changes in Young’s modulus of the steel were attributed to exposure to high temperatures, causing significant vibration within the steel atoms and increasing the distance between atoms, thereby reducing tensile strength. The influence of impurities may also be a factor affecting tensile strength. The tests also concluded that the recycled steel construction waste was a brittle material with an average V-notch toughness of 24J.